Methodology of Analysis of Sacred Music of the 20th Century (on the Example of Orthodox Tradition) - Sheludyakova, Oxana Ye. (Music Scholarship / Problemy Muzykal'noj Nauki, 2010)
The article is devoted to methodology of analysis of Russian sacred compositions. The author suggests that sacred music presents a special type of musical culture and its analysis should involve a number of approaches, including musicological, philosophical, cultural, theological, liturgical, musical-historical, and musical-theoretical. The author reveals appropriate types of research of a number of parameters: the purpose of music, number and type of performers, the degree of reliance on the canonical model of the genre, ways of text production, singing style, the presence of canonical chants, etc. Keywords: choral music, sacred music, Orthodox chants